Implementation of the 2013 Curriculum at MTs AL-Abraar - Neliwati; Devi Indah Sari (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
This study aims to analyse the Implementation of the 2013 Curriculum at Mts Al-Abraar. The purpose of this study is to find out how the effectiveness of the 2013 curriculum is compared to the previous curriculum, the constraints or obstacles occurred during the implementation of the 2013 curriculum, the respond of educators and students when using the 2013 curriculum which is far different from the previous curriculum, the things prepared in using the 2013 curriculum and the benefits or advantages for students and also educators when using the 2013 curriculum. This study uses qualitative methods because researchers consider the problems studied to be quite complex and dynamic so that the data obtained from the informants is captured using a more natural method, namely direct interviews with the informants so that natural answers are obtained. The conclusion that the researchers got from this mini research or observation is that schools have implemented the 2013 curriculum, but have not been able to achieve maximum implementation of the 2013 curriculum, because sometimes in learning they still use the KTSP system, such as teachers are more active than students, more teachers speak from on students. And this can happen because one of them is inadequate school facilities because in order to achieve successful implementation of the 2013 curriculum, adequate school facilities are also needed, such as infocus and others.